Problem reformy kan. 1095 KPK - Góralski, Wojciech (Ius Matrimoniale, 2016)
In comparison to previous version of the Code of Canon Law, the introduction to the current Code of Canon Law can. 1095, ff. 1-3 constitutes novum. That is why there were numerous doubts concerning the “reading” of the legal norm. Whereas f. 1 of the canon did not cause any trouble in its reading and use, ff. 2-3 did. Year by year both the Roman Rota doctrine and judicature were making efforts to enable understanding the conception of the legislator which was preceded by a long process of editing the legal norm. Popes’ Magisterium, especially that of John Paul II, were of huge importance here. In previous years the relations of f. and f. 3 of legal norm has become a subject of discussion, and especially the question whether incapacitas assumendi (f. 3) is an autonomous figure. Despite the stance taken by the Roman Rota towards the autonomy of f. 3, there have been several attempts to locate incapacitas assumendini within the lack of psychological act of marriage consent. As a result, a reform of can. 1095 in de lege ferenda mode has been proposed. The proposal of H. Franceschi seems right in this case.